Histopathology of new-onset refractory status epilepticus (NORSE) in adults. (December 2021) - Suchdev, Kushak; Kupsky, William J.; Mittal, Sandeep; Shah, Aashit K.
Highlights: New onset refractory status epilepticus. Pathology of NORSE. Refractory status epilepticus. Surgery for status epilepticus. Abstract: Objective: new-onset refractory status epilepticus (NORSE) is defined as de novo refractory seizures occurring in previously healthy adults, without a clear underlying etiology. Due to refractory seizures and insufficient understanding of pathophysiology, management of these patients remains challenging and often leads to poor clinical outcomes. Various infectious and autoimmune mechanisms have been proposed but have not been validated and a large number of patients are thus labeled 'cryptogenic'. Moreover, histopathological findings have rarely been described in NORSE and are usually autopsy evaluations. In this paper, we describe the clinical correlates and histopathological findings in patients presenting with NORSE. Methods: A case series of five patients with NORSE who underwent neurosurgical intervention and had histopathological examination during their acute clinical course. Results: In all patients, status epileptics was refractory to treatment with antiseizure drugs (ASDs) and anesthetic agents. Autoimmune work-up revealed elevated titer of anti-GAD antibody in one patient but was unremarkable in others. Empiric use of immunomodulation therapy in three patients did not lead to cessation of status epilepticus (SE). Due to failure of prolonged medical management, three patients underwent palliative surgery for resection of epileptogenic tissue whereas the other two had diagnostic brain biopsy. Histopathology obtained during biopsy revealed evidence of vasculitis in one and necrotizing vasculopathy in another. The patient with anti-GAD antibodies had evidence of lymphocytic infiltration in limbic structures. The remaining two had nonspecific histopathological findings. Significance: Although our findings are limited by a small number of patients, it adds to the growing premise of NORSE being related to an underlying autoimmune process. Additional studies, especially with histopathological data are needed to better understand this devastating disorder.